2013
DOI: 10.1021/jo4002867
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Studies of Epoxides and Related Compounds

Abstract: Gas phase heats of formation for the our butene oxide isomers are reported. They were obtained by measuring the condensed-phase heat of reduction to the corresponding alcohol using reaction calorimetry. Heats of vaporization were determined, and allow gas-phase heats of formation to be obtained. The experimental measurements are compared to calculations obtained using a variety of computational methods. Overall, the G3 and CBS-APNO methods agree quite well with the experimental data. The influence of alkyl sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…For example, epoxide groups present in GO are particularly unstable and likely to react, due to the inductive effect of the oxygen and the unfavourable ring strain. 45 This may contribute to the observed hole formation (Fig. 4) in the GO sheets [16][17][18] where epoxides arise.…”
mentioning
confidence: 95%
“…For example, epoxide groups present in GO are particularly unstable and likely to react, due to the inductive effect of the oxygen and the unfavourable ring strain. 45 This may contribute to the observed hole formation (Fig. 4) in the GO sheets [16][17][18] where epoxides arise.…”
mentioning
confidence: 95%
“…Given that relief of ring strain is the driving force for the formal homo‐Nazarov cyclization, it is conceivable that similar ring‐opening cyclization would be possible if the cyclopropane ( E strain =27.5 kcal mol −1 ) were replaced with other polarizable ring systems. In that regard, the prime candidates to probe this hypothesis include: cyclopropenes ( E strain =54 kcal mol −1 ); epoxides ( E strain =26.3 kcal mol −1 ); aziridines ( E strain =26.7 kcal mol −1 ); alkylidene cyclopropanes ( E strain =39.5 kcal mol −1 ); and cyclobutanes ( E strain =26 kcal mol −1 ).…”
Section: Substrate‐based Dos Approachesmentioning
confidence: 99%
“…It is now acknowledged that measured enthalpy of formation data on species with three-membered rings of any type are simultaneously few in number 1 and reliability is occasionally suspect. 2 Likewise, measured proton affinities are almost totally absent for these species. Paralleling our recent publication, 3 using cyclopropanone (1), aziridine (2), and oxirane (3) as archetypes, the assembled species for our current study are shown in Fig.…”
Section: Introductionmentioning
confidence: 97%
“…2 Likewise, measured proton affinities are almost totally absent for these species. Paralleling our recent publication, 3 using cyclopropanone (1), aziridine (2), and oxirane (3) as archetypes, the assembled species for our current study are shown in Fig. 1: aziridine-2-one (also called ␣-lactam, 4), oxirane-2-one (also called ␣-acetolactone, 5), 1,2-diaziridine-3-one (6), 1,2-dioxirane-3-one (also called carbon trioxide, 7), 1,2-oxaziridine-3-one (8), cyclopropane-1,2-dione (9), aziridine-2,3-dione (also called oximide, 10), and oxirane-2,3-dione (also called oxalic anhydride, 11); we recently also studied the associated enol tautomers such as the two rotamers of 2-hydroxycyclopropenol (9a) corresponding to cyclopropane-1,2-dione (9).…”
Section: Introductionmentioning
confidence: 97%